Analisis Efektivitas Kampanye Iklan Digital dalam Meningkatkan Citra Lembaga Pendidikan Islam ( Studi kasus : MI. Bahrul Ulum Watupanjang - Krucil ) - Unzil Al Huda (Advances In Education Journal, 2025)
This study aims to analyze the effectiveness of digital advertising campaigns in improving the image of Islamic educational institutions at MI Bahrul Ulum, Watupanjang Village, Krucil District. The research location was chosen because of its characteristics as a rural area with limited access to technology but with untapped potential for digital marketing development. The research method used is descriptive qualitative with a case study approach, involving data collection through in-depth interviews, participatory observation, and document analysis. Research informants consisted of madrasah administrators, teachers, parents, and the surrounding community. The results showed that the digital advertising campaign conducted through social media such as WhatsApp, Instagram, and Facebook successfully expanded the reach of information and increased public awareness of the existence and advantages of MI Bahrul Ulum. Content that emphasized Islamic values and modern learning was able to attract interest and build audience trust. However, limitations in human resources for content management and unstable internet access remain major challenges in maximizing the effectiveness of digital campaigns. In conclusion, digital advertising campaigns play a crucial role in strengthening MI Bahrul Ulum's image as a credible and innovative Islamic educational institution. Enhancing the capacity of administrators and improving technological infrastructure are essential for optimizing future digital marketing strategies.